YIELD OF SPUTUM CULURE AND SENSITIVITY IN CHRONIC OBSTRUCTIVE AIRWAYS DISEASE PATIENTS (The Research of Medical Science Review, 2025)
Background: Chronic Obstructive Pulmonary Disease (COPD) continues to be a serious global health issue, ranking high among the leading causes of illness and death worldwide. One of the most challenging aspects of managing COPD is dealing with acute exacerbations (AECOPD), which often accelerate disease progression, lead to more frequent hospitalizations, and significantly increase healthcare expenses. A major cause of these flare-ups is bacterial infection, making it crucial to identify the specific bacteria involved and understand how they respond to antibiotics. This knowledge is key to choosing the right treatment and improving recovery outcomes. Objective: The goal of this study was to assess how effective sputum culture and sensitivity testing are in detecting bacterial infections during AECOPD episodes. Methods: We conducted a prospective observational study over a three-month span—from 8 January to 8 April 2025—at Hayatabad Medical Complex in Peshawar, Pakistan. The study included 200 patients who were clinically and spirometrically diagnosed with AECOPD. Each patient provided a sputum sample, which was analyzed using standard laboratory procedures to identify bacteria and determine which antibiotics the bacteria were most sensitive to. Results: Of the 200 samples collected, 120 (60%) showed positive bacterial growth. The most commonly detected bacteria were Streptococcus pneumoniae (35%), Haemophilus influenzae (25%), Klebsiella pneumoniae (20%), and Pseudomonas aeruginosa (15%). Sensitivity testing revealed that S. pneumoniae and H. influenzae responded well to amoxicillin-clavulanate and levofloxacin. Meanwhile, K. pneumoniae and P. aeruginosa showed better sensitivity to imipenem and amikacin.Conclusion: This study highlights the value of performing sputum culture and antibiotic sensitivity testing in patients with AECOPD. Tailoring antibiotic therapy based on specific bacterial identification can enhance treatment effectiveness, reduce unnecessary use of broad-spectrum antibiotics, and help combat the growing threat of antimicrobial resistance in respiratory infections.